Association Between the Presence of Female-Specific Tumors and Aggressive Clinicopathological Features in Papillary Thyroid Cancer: A Retrospective Analysis of 9,822 Cases - Zhang, Jiao; Zhou, Le; Dionigi, Gianlorenzo; Zhang, Daqi; Zhao, Lina; Liang, Nan; Xue, Gaofeng; Sun, Hui (Frontiers in Oncology, 2021)
Objective To investigate the association between the presence of female-specific tumors and aggressive clinicopathological features in papillary thyroid cancer (PTC). Methods This study retrospectively analyzed 9,822 female cases between June 2008 and December 2017. Odds ratios and corresponding 95% confidence intervals were calculated. Findings were stratified by age and body mass index (BMI) in different models. Results 1443/9822 (14.7%) patients with PTC had a female-specific tumor. Presence of a benign breast mass was an independent risk factor for a primary PTC lesion > 1 cm in diameter (adjusted OR = 1.446, 95% CI 1.136–1.840, P = 0.003), but a protective factor against extrathyroidal extension of PTC (adjusted OR = 0.650, 95%CI 0.500–0.845, P = 0.001). Presence of a benign uterine mass was an independent risk factor for multifocal PTC (adjusted OR = 1.305, 95%CI 1.113–1.531, P = 0.001). Analyses stratified by age and BMI revealed the presence of a benign breast mass was an independent risk factor for a primary PTC lesion > 1 cm in diameter in patients aged <36 years (adjusted OR = 1.711, 95% CI 1.063–2.754, P = 0.027), and a protective factor against extrathyroidal extension of PTC in patients aged ≥36 - <42 years (OR adjusted = 0.533, 95% CI 0.302–0.941, P = 0.030) or with a BMI ≥ 23.4 kg/m2 (BMI ≥ 23.4 to < 25.7 kg/m2, adjusted OR = 0.441, 95% CI 0.246–0.792, P = 0.006; BMI ≥25.7 kg/m2, adjusted OR = 0.558, 95% CI 0.315–0.998, P2 = 0.045). Presence of a benign uterine mass was an independent risk factor for multifocal PTC in patients aged ≥49 years (adjusted OR = 1.397, 95% CI 1.088–1.793, P = 0.009) or with a BMI <21.5 kg/m2 (OR adjusted = 1.745, 95% CI 1.214–2.509, P = 0.003). Conclusion The presence of a benign breast mass was an independent risk factor for a primary PTC lesion > 1 cm in diameter and a protective factor against extrathyroidal extension of PTC, while the presence of a benign uterine mass was an independent risk factor for multifocal PTC. Data from this study may help surgeons propose more personalized treatment plans when encountering patients with PTC and female-specific benign tumors.